3×3 basketball: performance characteristics and changes during elite tournament competition - Montgomery, P. G.; Maloney, B. D. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To determine the changes in game performance during tournament play of elite 3×3 basketball. Methods: A total of 361 men and 208 women competing in selected international tournaments had game demands assessed by wearable technology (global positioning system, inertial sensor, and heart rate) along with postgame blood lactate and perceived responses. Differences in the means for selected variables between games were compared using magnitude-based inferences and reported with effect size and associated confidence limits (CL), along with the percentage difference (ES; ±90% CL, %difference) of log-transformed data. Results: No clear differences were seen over a tournament period in PlayerLoad™ or PlayerLoad/minute. Tournament competition elicits variable changes between games for all inertial measures. Average peak heart rate was 198 (10) and 198 (9) beats/min, and average game heart rate was 164 (12) and 165 (18) beats/min for men and women, respectively, with no change between games. Average game lactate was 6.3 (2.4) and 6.1 (2.2) mmol/L for men and women, respectively. Average game ratings of perceived exertion were 5.7 (2.1) and 5.4 (2.0) AU for men and women, respectively. Although lactate and ratings of perceived exertion were variable between games, there was no difference over a tournament. Conclusions: The physical and physiological demands of elite 3×3 games over the duration of a tournament are similar regardless of pool or championship rounds. This may imply that maintaining technical and strategic aspects leads to success rather than minimizing fatigue through superior physical preparation. However, the physiological responses are high; caution is warranted in being underprepared for these demands in tournament play.